2022
DOI: 10.3390/en15124389
|View full text |Cite
|
Sign up to set email alerts
|

Improved Body Force Model for Estimating Off-Design Axial Compressor Performance

Abstract: Based on the COMSOL software, body forces substituted into the Reynolds-averaged Navier–Stokes (RANS) equations as the source terms instead of the actual blade rows were improved to better predict the compressor performance. Improvements in parallel body force modeling were implemented, central to which were the local flow quantities. This ensured accurate and reliable off-design performance prediction. The parallel force magnitude mainly depended on the meridional entropy gradient extracted from three-dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Due to the circumferential uniformity of the grid used to solve the flow in the fan duct, the blockage effect of the presence of blades on the flow cannot be considered. Research [30][31][32] has shown that disregarding the blockage effect of blades can have a certain impact on the accuracy of calculation results, especially for near-chocking conditions. Therefore, this article introduces the blockage coefficient b was introduced for considering the circumferential thickness of the blade during calculation, which can be calculated as follows: The relationship between the rotational speed of the fan spool and resistance torque under different operating conditions was obtained using numerical simulation results, as shown in Figure 8.…”
Section: Numerical Simulation Of Fan Windmilling Conditionmentioning
confidence: 99%
“…Due to the circumferential uniformity of the grid used to solve the flow in the fan duct, the blockage effect of the presence of blades on the flow cannot be considered. Research [30][31][32] has shown that disregarding the blockage effect of blades can have a certain impact on the accuracy of calculation results, especially for near-chocking conditions. Therefore, this article introduces the blockage coefficient b was introduced for considering the circumferential thickness of the blade during calculation, which can be calculated as follows: The relationship between the rotational speed of the fan spool and resistance torque under different operating conditions was obtained using numerical simulation results, as shown in Figure 8.…”
Section: Numerical Simulation Of Fan Windmilling Conditionmentioning
confidence: 99%
“…Several studies have focused on the characteristics of various axial compressors and the elements influencing their performance (Huang et al, 2022;Babin et al, 2023). For instance, Blinov and Zubkov (2020) investigated the effect of blade row defects on the performance of a compressor.…”
Section: Introductionmentioning
confidence: 99%